(untitled) (Journal of Advanced Research in Social Sciences, 2023)
This article describes the Rapid Enlightenment Process (REP). An intervention focused on entrepreneurs and business executives to increase their psychological resources. The treatment has four components: (1) Understanding of the survival mind; 2) Acceptance; (3) Recontextualization; and 4) Adoption of the “Enlightened Perspectives,” helpful hermeneutics and heuristics to sustain the experience of peace and positive emotions until it becomes a habit. The paper builds on arguments and ideas presented in a theoretical model with the primary objective of formulating a set of propositions detailing factors affecting the REP and the effectiveness at each of its phases. Since REP is an innovation lacking empirical evidence, its claims are supported by a logic model referencing theories and research in the field of positive psychology, neuroscience, and an integrated framework of emotional theories. This paper aims to contribute to the well-being intervention literature to guide empirical research, and ultimately to evaluate REP.